A Review on Puerulus (Panulirus spp.) Resource Utilization in Indonesia Based on the Sense of Hearing: Auditory Receptor Organs - Hari Subagio; Evron Asrial; Yusnaini Yusnaini; Nurul Rosana; Gatut Bintoro; Nuhman Nuhman; I Made Kawan (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchThe mortality of lobster seeds by predators in the first year is 96.0-99.4%It takes technology to catch seeds before being eaten by predatorsApplication of sound wave-based attractor technology to lobstersDo lobsters have the ability to hear sound waves?The lobster's sense of hearing begins to function from the puerulus stage AbstractIndonesia is a country that produces abundant lobster seeds (puerulus), however, there is a paradox, where natural mortality in the first year since entering the settlement phase can reach 96.0-99.4%. The use of lobster resources, especially in the puerulus stage, for cultivation, is very strategic. Therefore, it is necessary to improve puerulus fishing technology. In the capture fisheries sector, the use of the sense of hearing in fish resources has been carried out to increase catch productivity, by utilizing sound wave-based attractors' technology. For lobster resources, to what extent is this technology applicable? Underwater sound waves are a phenomenon of compression and expansion of a medium as sound energy passes through it. This aspect of the study is still new and very prospective. The purpose of this review article is to answer some basic questions: Can lobsters be able to hear sounds that come from their surroundings, since when do lobsters sense of hearing begin to function, and anatomically what kind of auditory organs are in lobsters. The results of the review conclude as follows: lobsters have senses that are able to perceive or listen to sound waves (sound) from their surrounding environment, this ability has been possessed by lobsters since they were in the postlarva or puerulus stage. Anatomically, the organs that act as the sense of hearing in lobsters are: receptors on the body surface, chordotonal organs and statocyst organs.